Levistilide A Promotes Expansion of Human Umbilical Cord Blood Hematopoietic Stem Cells by Enhancing Antioxidant Activity - He, Mei; Xu, Hui; Liu, Guangju; Yang, Ming; Zhang, Wenshan; Li, Yafang; Zhang, Hexiao; Wang, Chaoqun; Zhang, Yiran; Liu, Xiaolei; Xu, Shiqi; Ding, Yahui; et al. (Frontiers in Pharmacology, 2022)
A lack of approaches for expanding human hematopoietic stem cells (hHSCs) along with retainable capability of multipotential differentiation still limits the application of HSC-based therapy. Here we show a phthalide derivative, levistilide A (LA), can serve as a promising molecule to expand functional human umbilical cord blood (UCB) HSCs ex vivo. An in-house screen identified LA out of 9 natural products as an outstanding candidate for hHSCs expansion. Additionally, our data indicated that LA treatment not only increased the numbers of phenotype-defined HSCs, but also enhanced their colony formation ability. Xenotransplantation assays showed that LA treatment could promote rapid engraftment of hHSCs with multilineage differentiation. Further experiments revealed that LA enhanced the antioxidant activity of hHSCs by reducing intracellular and mitochondrial reactive oxygen species (ROS) levels. The identification of LA provides a new strategy in solving the clinical issue of limited numbers of UCB HSCs.